Examining FGC Survivor and FGC Impacted Community Involvement Behind FGM/C Legislation in the United States: A Response to Bader's “From the War on Terror to the Moral Crusade Against Female Genital Mutilation: Anti-Muslim Racism and Femonationalism in the United States” - Taher, Mariya (Violence against women, 2023)
As an American-born woman who grew up as a South Asian Dawoodi Bohra Muslim, I have been aware of female genital mutilation/cutting (FGM/C) my entire life. So I immediately agreed to give commentary on “From the War on Terror to the Moral Crusade Against Female Genital Mutilation: Anti-Muslim Racism and Femonationalisim in the United States” by Dina Bader. While I do not necessarily disagree with Bader's observations, I provide additional context to better understand the history of our current FGM/C laws in this country and the influence survivors and advocates’ have had in shaping them.